CATUR PURUSA ARTHA SEBAGAI DASAR KEGIATAN USAHA LEMBAGA PERKREDITAN DESA (LPD) DI DESA PAKRAMAN KIKIAN - Pancadana, Dewa Made; Oka Parwata, A.A. Gede (Kertha Semaya : Journal Ilmu Hukum, 2013)
The researchers' goal is to conduct research to identify and analyze the legal basis Catur Purusa Artha which serve as the basis for operations Village Credit Institutions (LPD) Kikian Pakraman village and how the implementation of the Elements of Catur Purusa Artha in operations The Village Financial Credit Institute DesaPakraman Kikian. The research method used in this paper is the method of empirical legal research, specification research is descriptive. Source of data used is primary data collected directly in the field and secondary data including primary legal materials, secondary and tertiary. Based on these results, it can be concluded as follows: 1. concept underlying Catur Purusa Artha as the basis of business activity The Village Financial Credit Institute DesaPakraman Kikian is religious law or doctrine derived from Hinduism's Holy Vedas 2. Catur Purusa Artha comprises four elements, namely Dharma, Artha, Kama Moksha. The operations of The Village Financial Credit Institute Desa Pakraman Kikian should should be based on kindness or dharma as it leads to the advantage that artha with profits going to fulfill a desire or kama of society so that when the desire or kama, moksha has been fulfilled, in this case defined as happiness will come true.
Keywords: The Village Financial Credit Institute, Catur Purusa Artha